Shakespeare's cinema of love : a study in genre and influence - White, R. S. (Manchester Shakespeare collection, 2016)
Shakespeare's cinema of love addresses the question, how much has Shakespeare influenced modern film genres? Convincing arguments are made for the links between his comedies of love and genres such as 'screwball' comedy, musicals, romantic comedy and tragic love films.